Government Policy, Empowerment and Community Participation in Sustainable Tourism Development in Ecotourism Mangrove Lembung Pamekasan - Hanifah Nur Aqilah; Darul Islam (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Sustainable tourism development has emerged as a primary emphasis in numerous development programs in Indonesia. Sustainable tourism encompasses three primary dimensions: economic, social, and environmental, engaging multiple stakeholders in the process. This study aimed to assess the impact of government policies, empowerment, and community participation on the advancement of sustainable tourism in the Lembung Pamekasan mangrove ecotourism sector. This research is a quantitative analysis. The study population comprised the community of Lembung Village, Galis, with a sample of 94 respondents obtained by purposive sampling techniques. Data analysis employed multiple linear regression utilising SPSS software. The study indicated that government policies positively and significantly influence the growth of sustainable tourism. Community empowerment exerted a good and important influence on the advancement of sustainable tourism. Community participation exerted a good and important influence on the advancement of sustainable tourism. Government policies, empowerment, and community participation concurrently exerted a favourable and significant influence on the advancement of sustainable tourism in the Lembung Pamekasan mangrove ecotourism.